Host innate immune responses and microbiome profile of neonatal calves challenged with Cryptosporidium parvum and the effect of bovine colostrum supplementation - Gamsjäger, Lisa; Cirone, Karina M.; Schluessel, Steffany; Campsall, Mackenzie; Herik, Aydin; Lahiri, Priyoshi; Young, Daniel; Dufour, Antoine; Sapountzis, Panagiotis; Otani, Saria; Gomez, Diego E.; Windeyer, M. Claire; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Calves are highly susceptible to gastrointestinal infection with Cryptosporidium parvum (C. parvum), which can result in watery diarrhea and eventually death or impaired development. With little to no effective therapeutics, understanding the host’s microbiota and pathogen interaction at the mucosal immune system has been critical to identify and test novel control strategies. We used an experimental model of C. parvum challenge in neonatal calves to describe the clinical signs and mucosal innate immune and microbiota hallmarks in the ileum and colon during cryptosporidiosis and investigated the impact of supplemental colostrum feeding on C. parvum infection. The C. parvum challenged calves experienced clinical signs including pyrexia and diarrhea 5 days post challenge. These calves showed ulcerative neutrophil ileitis with a proteomic signature driven by inflammatory effectors, including reactive oxygen species and myeloperoxidases. Colitis was also noticed with an aggravated mucin barrier depletion and lack of full filled mucin granule in goblet cells. The C. parvum challenged calves also displayed a pronounced dysbiosis with a high prevalence of Clostridium species (spp.) and number of exotoxins, adherence factors, and secretion systems related to Clostridium spp. and other enteropathogens, including Campylobacter spp., Escherichia sp., Shigella spp., and Listeria spp. Daily supplementation with a high-quality bovine colostrum product mitigated some of the clinical signs and modulated the gut immune response and concomitant microbiota to a pattern more similar to that of healthy unchallenged calves.